LOGISTICS OPPORTUNITIES OF THE REPUBLIC OF UZBEKISTAN WHY FOR CHINA? - Omadjon Tavakkaljon ugli Kodirjonov; Khusanboy Madaminjonovich Muminov (Journals Park Publishing, 2024)
In this article, the breakdown of relations between the United States of America, India, Pakistan, Russia, NATO and the People's Republic of China and, as a result, the increasing importance of the logistics system of the Republic of Uzbekistan for China. It will be explained how the Republic of Uzbekistan will benefit from this.
Keywords: railway, pipeline, sea routes, economic communication, export, import.